Comprehensive Unit-based Safety Program (CUSP) to Improve Patient Experience: How a Hospital Enhanced Care Transitions and Discharge Processes. Issue 4 (October 2016) - Pottenger, Brent C.; Davis, Richard O.; Miller, Joanne; Allen, Lisa; Sawyer, Melinda; Pronovost, Peter J.
Abstract : Objective: To determine whether Comprehensive Unit-based Safety Program (CUSP) teams could be used to enhance patient experience by improving care transitions and discharge processes in a 318-bed community hospital. Methods: In 2015, CUSP teams produced feasible solutions by participating in a design-thinking initiative, coupled with performance improvement tools involving data analytics and peer-learning communities. Teams completed a 90-day sprint challenge, involving weekly meetings, monthly department leader meetings, and progress trackers. The Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) survey was used, and the percent top (best) scores were reported for overall hospital ratings, discharge information, and care transitions. Results: The percentage of patients choosing the top score increased from 61.0% preintervention to 68.0% postintervention for overall hospital rating and from 71.4% to 80.7% for recommending the hospital. The top scores increased from 76.0% preintervention to 84.5% postintervention for the discharge information domain and from 49.2% to 53.6% for the care transitions domain. Conclusion: CUSP teams improved patient experience. The teams could expand their scope to be the unit-level resource focused not only on safety but also on external quality measures to which patient experience is a broad category for HCAHPS scores, and potentially on value in future work.